ChemInform Abstract: Crystal Structure of Bis(dimethylammonium) Hexaaquanickel(II) Bis(sulfate) Dihydrate. Issue 5 (February 2015) - Held, Peter
Abstract Large (Me2NH2)2 [Ni(H2O)6] (SO4)2·2H2O single crystals (up to 4 mm crystal size) are grown from an aqueous solution of NiSO4, Me2NH, and H2SO4 (1:2:1) by slow solvent evaporation (room temp., 12 weeks).